THE SPECIES AND ABUNDANCE OF BIVALVIA SPAT IN MANGROVE FOREST SUBSTRATE IN RUPAT ISLAND, BENGKALIS - Oktavian, Rizki; Nasution, Syafruddin; Zulkifli, Zulkifli (Asian Journal of Aquatic Sciences, 2025)
The availability of bivalve spat has a strategic role in ensuring the sustainability of bivalve communities in aquatic ecosystems. This study aims to determine the species, abundance, and timing of bivalve spat settled on the basic substrate of mangrove forest in the intertidal zone of Rupat Island. This research was conducted in June - October 2017. The research was located in the intertidal zone, which is divided into three subzones: upper, middle, and lower. To collect spat bivalve using a net collector, like a tray. This research method was a survey method. The results showed that the bivalve spat had three types: Pilsbryoconcha exilis spat, Polymesoda expansa, and Pharella acutidens. The average abundance is 4.06 ind/m2; the highest abundance of bivalve spats was at the lower subzone, 2.13 ind/m2. The lower subzone was adjacent to the sea and was affected by the tides. From the monthly sampling, October was the highest, with an average abundance of 1.2 ind/m2. Spat catches in June-October were low, and the possibility of a recruit peak of bivalve spat had not happened yet.